Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
tamanh nguyen

với a > 0, b > 0 thì \(\sqrt{\dfrac{a}{b}}+\dfrac{a}{b}\sqrt{\dfrac{b}{a}}\)bằng:

a) 2

b) \(\dfrac{2\sqrt{ab}}{b}\)

c) \(\sqrt{\dfrac{a}{b}}\)

d) \(\sqrt{\dfrac{2a}{b}}\)

Monkey D. Luffy
17 tháng 11 2021 lúc 9:22

\(=\dfrac{\sqrt{ab}}{b}+\sqrt{\dfrac{a^2b}{b^2a}}=\dfrac{\sqrt{ab}}{b}+\sqrt{\dfrac{a}{b}}=\dfrac{\sqrt{ab}}{b}+\dfrac{\sqrt{ab}}{b}=\dfrac{2\sqrt{ab}}{b}\left(B\right)\)

ILoveMath
17 tháng 11 2021 lúc 9:23

B

Chanh Xanh
17 tháng 11 2021 lúc 9:23

B